The CCL3-CCR1 axis promotes corticotomy-accelerated orthodontic tooth movement by regulating M1 macrophage polarization - Yuefan Ma; Yiwen Huang; Jiayi Zhang; Yutong Zhong; Han Chen; Jingang Xiao; Xiaomei Xu (BMC Oral Health, 2026)
Abstract Background Corticotomy promotes bone remodeling through the regional acceleratory phenomenon (RAP) and is a commonly used surgical procedure to accelerate orthodontic tooth movement (OTM). However, the molecular mechanisms underlying RAP remain incompletely understood, which limits the development of non‑invasive strategies to accelerate tooth movement based on this phenomenon. Accumulating evidence supports that M1 macrophages serve as key effector cells in RAP. C‑C motif chemokine ligand 3 (CCL3) and its receptors are important regulators of macrophage polarization, but their specific role in corticotomy‑induced RAP has not yet been elucidated. Methods After establishing a rat model of orthodontic tooth movement combined with corticotomy (OTM + CO) in male rats, changes in the CCL3‑CCR1 axis and in macrophages during corticotomy‑accelerated osteoclast differentiation were examined by reverse transcription‑polymerase chain reaction (RT‑qPCR), Western blotting, and immunofluorescence staining. Subsequently, RAW264.7 cells were treated with recombinant CCL3 (rCCL3) or transfected with lentivirus to modulate the CCL3‑CCR1 axis, and the effect of this axis on macrophage polarization was assessed using flow cytometry, among other methods. Finally, following local periodontal injection of the CCR1 antagonist BX471 into the OTM + CO model, micro‑computed tomography (micro‑CT), hematoxylin and eosin (H&E) staining, and tartrate‑resistant acid phosphatase (TRAP) staining were employed to determine whether CCR1 inhibition in macrophages attenuates the corticotomy‑induced effects on tooth movement distance, bone resorption, and macrophage polarization status. Results Corticotomy specifically activated the CCL3-CCR1 signaling axis in mechanically stimulated alveolar bone and significantly upregulated the expression of M1 macrophage markers. Recombinant CCL3 enhanced macrophage polarization toward the M1 phenotype through CCR1 binding. This polarization effect was significantly reversed when CCR1 expression was knocked down in macrophages, as determined by lentiviral transduction. Animal experiments further demonstrated that CCR1 inhibition effectively blocked corticotomy-induced macrophage polarization toward the M1 phenotype and suppressed bone remodeling acceleration. Conclusions The CCL3-CCR1 axis plays an important role in corticotomy-induced RAP through driving M1 macrophage polarization, thereby promoting alveolar bone remodeling and accelerating OTM. These findings revealed a novel mechanism underlying corticotomy-promoted tooth movement and offered important theoretical support for the development of non-surgical strategies to increase the efficiency of orthodontic treatment.